Work–Life Balance of the Employed Population During the Emergency Situation of COVID-19 in Latvia - Lonska, Jelena; Mietule, Iveta; Litavniece, Lienite; Arbidane, Iluta; Vanadzins, Ivars; Matisane, Linda; Paegle, Linda (Frontiers in Psychology, 2021)
All the employees face the challenge of finding the right work-life balance. The ability of employees to deal with the successful combining of work, family responsibilities, and personal life is crucial for both employers and family members of employees. During the COVID-19 emergency situation, many people around the world were forced to work remotely. Initially, there were observed some certain expectations about the possibility of working from home as a positive factor that will promote work-life balance. However, over time, negative tendencies were also revealed, as employees were only one call or message away from the employer, and uncertainty and leisure time with family often created more stress. As many organizations and individuals were not ready for this sudden change, many mistakes were made, which further raised the issue of work-life balance. The aim of the research was to evaluate the flexibility of reconciling work and private life of Latvian employees in various socio-demographic groups during the COVID-19 emergency situation in spring 2020, to investigate how family life influenced employees’ ability to perform work duties, to find out if employees had any additional housework responsibilities and how their workload changed concerning housework amount during the COVID-19 emergency situation. The research is based on the data obtained in the survey of the Latvian employed population, which was conducted within the framework of the Latvian National Research Programme Project “CoLife” in the second half of 2020. As a result, the hypothesis of the research that all groups of employees experienced work-life balance difficulties during the COVID-19 emergency situation has been partially confirmed, i.e. women in the 18-44 age group and respondents with minor children in the household more likely faced difficulties of work-life balance. The scientific research methods that were used in the research are the monographic method, content analysis, survey, data processing with SPSS to determine the mutual independence of the data from the questionnaires.